Manufacturers News (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1952)
Shovel To further increase the efficiency in the production of their foundry sand, the American Silica Sand Co. has purchased a new and improved shovel that will be used for loading trucks at their Reynolds Pit. The [ ] new shovel will greatly facilitate winter mining operations and make possible larger winter shipments of the company's foundry sand. The Reynolds Pit is one of three sand pits in the Ottawa district owned by American Silica which produce sand that is refined for foundry use. Circle No. 1 Electric Switches The Crane Electric Co. has just announced the production of their R-1000, a new rotating limit switch designed to control the travel of any rotating device requiring interruption or establishment of electrical current after a predetermined number of revolutions. It is useful for machinery, lifts, and other power equipment. The switch is presented in a finished case, 16 gage, reinforced, with walls of sufficient strength to hold the entire mechanism and all the parts in accurate alignment. The worm gear combination has a 60 to 1 ratio, sufficient for most industrial uses. The number of revolutions can still be increased by using various combinations of driving sprockets, either on the shaft of the switch, or on the sprocket of the unit controlled by the switch itself. Circle No. 2